Electronic structure transformation in small bare Au clusters as seen by x-ray photoelectron spectroscopy. (16th December 2016) - Andersson, T; Zhang, C; Björneholm, O; Mikkelä, M-H; Jänkälä, K; Anin, D; Urpelainen, S; Huttula, M; Tchaplyguine, M
Abstract: Free bare gold clusters in the size range from few tens to few hundred atoms (≤1 nm dimensions) have been produced in a beam, and the size-dependent development of their full valence band including the 5 d and 6 s parts has been mapped 'on the fly' by synchrotron-based photoelectron spectroscopy. The Au 4 f core level has been also probed, and the cluster-specific Au 4 f ionization energies have been used to estimate the cluster size. The recorded in the present work valence spectra of the small clusters are compared with the spectra of the large clusters ( N ∼ 10 3 ) created by us using a magnetron-based gas aggregation source. The comparison shows a substantially narrower 5 d valence band and the decrease in its splitting for gold clusters in the size range of few hundred atoms and below. Our DFT calculations involving the pseudopotential method show that the 5 d band width of the ground state increases with the cluster size and by the size N = 20 becomes comparable with the experimental width of the valence photoelectron spectrum. Similar to the earlier observations on supported clusters we interpret our experimental and theoretical results as due to the undercoordination of a large fraction of atoms in the clusters with N ∼ 10 2 and below. The consequences of such electronic structure of small gold clusters are discussed in connection with their specific physical and chemical properties related to nanoplasmonics and nanocatalysis.